Nanoparticulate Quillaja saponin induces apoptosis in human leukemia cell lines with a high therapeutic index - Kefei Hu (Dove Medical Press, 2010)
Kefei Hu1, Saideh Berenjian1, Rolf Larsson2, Joachim Gullbo2, Peter Nygren3, Tanja Lövgren4, Bror Morein11Department of Medical Sciences, Section of Virology, Uppsala University, Uppsala, Sweden; 2Department of Medical Sciences, Uppsala University Hospital, Uppsala, Sweden; 3Department of Oncology, Radiology and Clinical Immunology, Uppsala University Hospital, Uppsala, Sweden; 4Department of Molecular Bioscience, Section for Veterinary Immunology and Virology, Swedish University of Agricultural Sciences, Uppsala, SwedenAbstract: Saponin fractions of Quillaja saponaria Molina (QS) have cytotoxic activity against cancer cells in vitro, but are too toxic to be useful in the clinic. The toxic effect was abolished by converting QS fractions into stable nanoparticles through the binding of QS to cholesterol. Two fractions of QS were selected for particle formation, one with an acyl-chain (ASAP) was used to form killing and growth-inhibiting (KGI) particles, and the other without the acyl-chain (DSAP) was used to formulate blocking and balancing effect (BBE) particles. KGI showed significant growth inhibiting and cancer cell-killing activities in nine of 10 cell lines while BBE showed that on one cell line. The monoblastoid lymphoma cell line U937 was selected for analyzing the mode of action. Low concentrations of KGI (0.5 and 2 µg/mL) induced irreversible exit from the cell cycle, differentiation measured by cytokine production, and eventually programmed cell death (apoptosis). Compared to normal human monocytes, the U937 cells were 30-fold more sensitive to KGI. The nontoxic BBE blocked the cell killing effect of KGI in a concentrationdependent manner. In conclusion, the formulation of QS into nanoparticles has the potential of becoming a new class of anticancer agents.Keywords: anticancer drug, Quillaja saponin, nanoparticle, apoptosis